Behavioural and neurogenomic responses of host workers to social parasite invasion in a social insect - A. Cini; R. Branconi; S. Patalano; R. Cervo; S. Sumner (Insectes Sociaux, 2020)
The strong coevolutionary arms race between social parasites and their hosts has dramatically shaped the life-history traits of both parties. One of the main strategies exhibited by hosts in response to parasitism is reproduction by host workers. We lack a mechanistic understanding of how these defence strategies unfold and, specifically, whether hosts exhibit more subtle strategies to reduce the costs of parasitism from the outset. Here we test the hypothesis that there are both behavioural and neurogenomic signatures of worker responses to parasitism, prior to overt expression in the form of egg-laying; we test this using the social parasite—social host system of the paper wasps Polistes sulcifer-Polistes dominula. We characterized individual workers’ position within the social interaction network of queenright and host colonies immediately after parasite usurpation, weeks before the workers’ reproductive rebellion is evident. Parasitism influenced network centrality measures, with workers in parasitized colonies showing increased connectedness and centrality compared to those in unparasitized ones. Next, we quantified brain gene expression levels for five genes related to physiological and behavioural phenotypes in Polistes wasps. The gene Imaginal disc growth factor ( Idgf4 ), thought to be responsive to changes in the social environment, was significantly down-regulated in workers from parasitized colonies; this may be an indication that parasitized workers are anticipating a shift toward a less worker-like phenotype in preparation for their reproductive rebellion. Our results provide the first evidence of early behavioural and neurogenomic responses of host workers toward the presence of an inquiline social parasite in a social insect.

WASP nest: a worldwide assessment of social Polistine nesting behavior - Sara E. Miller; Sarah E. Bluher; Emily Bell; Alessandro Cini; Rafael Carvalho da Silva; André Rodrigues de Souza; Kristine M. Gandia; Jennifer Jandt; Kevin Loope; Amanda Prato; Jonathan N. Pruitt; David Rankin; et al. (Ecology, 2018)
Cooperative breeding decreases the direct reproductive output of subordinate individuals, but cooperation can be evolutionarily favored when there are challenges or constraints to breeding independently. Environmental factors, including temperature, precipitation, latitude, high seasonality, and environmental harshness have been hypothesized to correlate with the presence of cooperative breeding. However, to test the relationship between cooperation and ecological constraints requires comparative data on the frequency and variation of cooperative breeding across differing environments, ideally replicated across multiple species. Paper wasps are primitively social species, forming colonies composed of reproductively active dominants and foraging subordinates. Adult female wasps, referred to as foundresses, initiate new colonies. Nests can be formed by a single solitary foundress (noncooperative) or by multiple foundress associations (cooperative). Cooperative behavior varies within and among species, making paper wasps species well suited to disentangling ecological correlates of variation in cooperative behavior. This data set reports the frequency and extent of cooperative nest founding for 87 paper wasp species. Data were assembled from more than 170 published sources, previously unpublished field observations, and photographs contributed by citizen scientists to online natural history repositories. The data set includes 25,872 nest observations and reports the cooperative behavioral decisions for 45,297 foundresses. Species names were updated to reflect modern taxonomic revisions. The type of substrate on which the nest was built is also included, when available. A smaller population‐level version of this data set found that the presence or absence of cooperative nesting in paper wasps was correlated with temperature stability and environmental harshness, but these variables did not predict the extent of cooperation within species. This expanded data set contains details about individual nests and further increases the power to address the relationship between the environment and the presence and extent of cooperative breeding. Beyond the ecological drivers of cooperation, these high‐resolution data will be useful for future studies examining the evolutionary consequences of variation in social behavior. This data set may be used for research or educational purposes provided that this data paper is cited.

Tracking the invasion of the alien fruit pest Drosophila suzukii in Europe - A. Cini; G. Anfora; L. A. Escudero-Colomar; A. Grassi; U. Santosuosso; G. Seljak; A. Papini (Journal of Pest Science, 2014)

Ovarian indexes as indicators of reproductive investment and egg-laying activity in social insects: a comparison among methods - A. Cini; S. Meconcelli; R. Cervo (Insectes Sociaux, 2013)

On the influence of spatial heterogeneity on an internal boundary layer at a short fetch - B. S. Murthy; R. Latha; Cini Sukumaran; A. Shivaji; S. Sivaramakrishnan (Journal of Earth System Science, 2009)